Antimicrobial protein produced by Bacillus Subtilis ATCC 21332 in the presence of Allium sativum - Nur Aishah A.W.; Ismatul Nurul Asyikin I.; Hairul Shahril M.; Maryam M.R.; Abdul Jalil A.K.; Rosfarizan M.; Hanina Mohd Noor; Salina Mat Radzi (2024)
Indexed by SCOPUS